Rethinking trade and commercial policy theories development perspectives - Ho, P. Sai-wing (Peter Sai-wing); Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2010)
This controversial book offers a unique approach to rethinking the trade and development literature and will therefore strongly appeal to researchers, academics, and students of trade and development as well as those involved in the history of economic thought.
pt. 1. Re-interpreting classical trade theories in a simple framework of capitalist development -- pt. 2. Re-examining "trade protection" arguments from perspectives of development.
Includes bibliographical references (p. [356]-386) and index.
Keywords: Commercial policy; Economic development; Electronic books